Inclusivity in Study Abroad: Supported Exchange Programs? - MacKenty, Mary (International Higher Education, 2020)
This article presents a critical look at the challenges and advantages of exchange programs in US study abroad. It asks whether better support for exchange students could lead to more inclusivity in study abroad.